É a língua umbra uma língua chocó?: uma primeira aproximação desde a linguística comparada - González , Simón (2025)
Umbra is a language that has recently become visible and addressed by linguistics. The most important proposal of genetic classification of this language places it among Choco languages. This paper discusses the idea of Umbra as Choco. To this end, the trajectory of this idea is reviewed and the comparative method on basic vocabulary is applied to deal with this proposal from the indicated procedure for the first time. Among the findings, no cognation relationships between Umbra and Choco words are found. Thus, this will trigger the proposal of a story of chronologically separated interlinguistic contacts.